Efficacy of N-Acetylcysteine (NAC) Against Malondialdehyde (MDA) Levels in Diabetic Cataracts: In vivo Study - Dining Pratidina; M. Hidayat; Andrini Ariesti (HM Publisher, 2022)
Background: Diabetes mellitus is a systemic condition that affects various organs, including the eyes. N-acetylcysteine ​​(NAC) functions as an antioxidant because it belongs to a thiol group synthesis glutathione. However, the availability of cysteine ​​in the body is only 15%, so cysteine ​​supplementation can help with oxidative stress in diabetic cataracts. That it will prevent the reaction of lipid peroxidase and the formation of PUFA in the lens membrane, which causes damage to lens cells and is characterized by an increase in malondialdehyde. This study aims to determine the comparison of malondialdehyde levels in the lenses of diabetic cataract rats given or without topical NAC. Methods: 36 rats were divided into the control group (received streptozotocin) and treatment group (received streptozotocin and topical NAC. Intraperitoneal injection of streptozotocin was given 90 mg/kg BW and performed once a week for 3 weeks. GDP examination was performed the next day after the rats fasted for 16 hours from the vein. In the tail, GDP > 110 mg/dl categorized as diabetes. Topical NAC was given 4 times per day for 3 weeks. At the end of the study, the lens was extracted for the measurement of malondialdehyde. Results: The mean MDA levels in the control group were higher (2.90±0.71nmol/ml) than in the treatment group (2.33±0.38nmol/ml), p<0.05. Conclusion: NAC was effective in reducing oxidative stress levels in diabetic cataract lenses by lowering MDA levels better than the group that did not receive MDA in vivo.